2023
DOI: 10.1038/s41598-023-31373-6
|View full text |Cite
|
Sign up to set email alerts
|

The association between body mass index, abdominal fatness, and weight change and the risk of adult asthma: a systematic review and meta-analysis of cohort studies

Abstract: Obesity has been associated with increased risk of adult asthma, however, not all studies have found a clear association between overweight and the incidence of asthma, and data on other adiposity measures have been limited. Hence, we aimed to summarize evidence on association between adiposity and adult asthma. Relevant studies were retrieved through searches conducted in PubMed, and EMBASE up to March 2021. A total of sixteen studies (63,952 cases and 1,161,169 participants) were included in the quantitative… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 49 publications
0
2
0
1
Order By: Relevance
“…30 While our results, in combination with recent Meta-analyses, indicate an association between obesity and respiratory diseases like asthma and CRS, it appears obesity may not be associated with the development of systemic vasculitis as seen in patients with EGPA. 31,32 Although not a small-vessel vasculitis, previous research has shown giant cell arteritis, a systemic vasculitis, was negatively associated with obesity. For these reasons, it may be possible that obesity does not play a role in the development of the small-vessel vasculitis seen in patients with EGPA, and further research on this topic is needed.…”
Section: Discussionmentioning
confidence: 99%
“…30 While our results, in combination with recent Meta-analyses, indicate an association between obesity and respiratory diseases like asthma and CRS, it appears obesity may not be associated with the development of systemic vasculitis as seen in patients with EGPA. 31,32 Although not a small-vessel vasculitis, previous research has shown giant cell arteritis, a systemic vasculitis, was negatively associated with obesity. For these reasons, it may be possible that obesity does not play a role in the development of the small-vessel vasculitis seen in patients with EGPA, and further research on this topic is needed.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, reduced lung tissue density, with more air, leads to decreased SUV values. Additionally, a systemic chronic inflammatory response often associated with higher BMI levels might have contributed to the correlation between the BMI and the lung SUV [ 35 , 36 , 37 ]: an elevated BMI has been linked to increased levels of pro-inflammatory cytokines and adipokines, which could potentially enhance metabolic activity and inflammation within lung tissue, thereby influencing SUV measurements [ 35 , 36 , 37 ]. However, we also investigated a potential association of diabetes and the pre-therapeutic lung SUV, which is another comorbidity with a known influence on metabolic activity and is associated with chronic inflammatory activity.…”
Section: Discussionmentioning
confidence: 99%
“…The NOS encompasses three domains: selection (scoring ranging from 0 to 5 for cross-sectional studies and 0 to 4 for cohort and case–control studies), comparability (scoring from 0 to 2), and outcome (scoring from 0 to 3). Depending on the cumulative scores attained, the studies were classified into three distinct groups: those with a very high risk of bias (0 to 3 points), high risk of bias (4 to 6 points), and low risk of bias (7 to 10 points) ( Herzog et al, 2013 ; Parasuaraman et al, 2023 ).…”
Section: Methodsmentioning
confidence: 99%